An Analysis of The Existence Level of West Javanese Traditional Beverages as Sundanese Cultural Heritage - Ramadhany, Nadya Nuansa; Iskandar, Ridwan; Sudono, Agus (Universitas Pendidikan Indonesia, 2020)
This research focuses on West Javanese traditional beverages. West Javanese traditional beverages are very varied in types. There are two main types of West Javanese traditional beverages in Bandung, namely hot and cold beverages. At present, the existence of traditional beverages is less popular compared to foreign beverages, such as Thai tea, boba milk tea, and so on. A real action in maintaining and preserving these traditional West Javanese beverages is a need. Therefore, this research aims to evaluate the exsistence level or popularity of traditional West Javanese beverages in Bandung, as a contribution to the literature on traditional beverages and a real action in presereving the beverages. This research employs a mix method research, with data collection techniques, using in-depth interviews, questionnaires, literature studies, and documentation studies. The purpose of this study is to determine whether traditional West Javanese beverages still exist in society, considering that in this era of globalization, food trends and people's tastes continue to change from time to time along with the influence of foreign cultures in Indonesia. The results of this study indicate that each type of traditional West Javanese beverages are at different level of existence, and the least exist beverages in society must be increased to avoid extinction.Â